Mineral release kinetics of common tropical green forages in the rumen of cattle - PAL, D T; SINGH, PRAMOD; PRASAD, C S; VERMA, SWATI; GOWDA, N K S (The Indian Journal of Animal Sciences, 2015)
The potential release of macro and micro minerals from six tropical green forages were determined by in sacco rumen degradability method. The release of minerals in the rumen were estimated in green forages (maize fodder, hybrid napier, doob grass, para grass, berseem and sunhemp) by incubating the forage samples for different periods, i.e. 10h, 24h, 48h and 72h in three adult cattle fitted with rumen cannula by in sacco nylon bag technique. The release of macro and micro minerals from experimental green forages were significantly (P Mg > P > Ca. Among the green forages, berseem and sunhemp showed highest release of various minerals in the rumen at different periods of incubation. Manganese (Mn) release was lowest among the micro minerals from experimental green forages in the rumen. The pattern of micro minerals release from green forages was as follows: Cu > Zn > Mn. Results obtained from the study concluded that the potential availability of various minerals in the rumen from different classes of green forages was different and this information may be useful in strategic supplementation of minerals to animals through green forages.